Peningkatan Minat dan Hasil Belajar Materi Memproduksi Teks Prosedur dengan Model Picture And Picture bagi Peserta Didik Kelas XI AKL 3 SMK Negeri 1 Slawi - Endah Setyo Rini (Cakrawala: Jurnal Pendidikan, 2021)
The purpose of this study is to find out the increased interest and learning outcomes of producing the text of the procedure of students of class XI AKL 3 SMK Negeri 1 Slawi Semester Gasal School Year 2019/2020 after following the learning to produce the procedure text with picture and picture model. This study uses class action research design (PTK) with 2 (two) cycles. The subject of this study was the result of producing the text of the procedure of students of class XI AKL 3 SMK Negeri 1 Slawi which amounted to 34 students. The results showed the use of picture and picture models can increase interest and learning outcomes in producing the text of student procedures. Increased interest is seen in the initial (pre-cycle) conditions of many passive learners to the final condition in cycle II of many active learners. The improvement in the results of learning to produce the text of the procedure was seen in the percentage of students who got a complete score (meet kkm) from the initial condition of the procedure text production value of only 52.94% then in cycle I increased to 67.65% and at the end of the second cycle increased to 91.17%.